Discourse Analysis of Xenophobia and Identity Politics in Contemporary South Africa - Awaliyah, Khofiyatul; Suharman, Yoga; Rahmahwati, Isti Nur (Department of International Relations, Universitas Brawijaya, 2026)
This study analyzes how identity politics and the apartheid system inherited from the colonial regime are reproduced into systems of exclusion and inclusion by segments of the local South African community towards other African migrants. The study focuses on lived experiences, as well as discursive and social practices of xenophobia in the postcolonial South African context using structured online interview research methods combined with Norman Fairclough's critical discourse analysis and a postcolonial theoretical framework, particularly the concepts of othering (Edward Said) and mimicry (Homi K. Bhabha) used to examine the understanding and experiences of other African communities regarding intra-racial discrimination and racial violence. Data were collected through online interviews with 17 informants from South Africa and Sub-Saharan African countries, as well as textual analysis of policy documents and official reports. The findings reveal that xenophobia is reproduced through symbolic exclusion, identity categorization, and the legitimization of public discourse that revives colonial hierarchies and dispositions. Identity politics reflected in xenophobia functions as a symbolic mechanism to maintain the boundaries of national identity and contributes to intra-racial violence in postcolonial South Africa.